Analisis Strategi Pengelolaan Pembelajaran Sekolah Dasar Pada Masa Adaptasi Tatanan Normal Baru Di Kota Kupang - Angelikus Koten (Jurnal Inovasi Kebijakan, 2021)
The strategy analysis of Elementary School learning management on New Normal Arrangement Adaptation Era in Kupang City is aimed: (1) To analyze the strategy of Elementary School learning process management in Kupang City during the adaptation of New Normal Arrangement; (2) To analyze the response and the Elementary Education Personnel prepared for applying the learning strategy on the New Normal Arrangement Adaptation Era in Kupang City; and (3) To analyze the availability of health facilities and students arrangement in Elementary School on the New Normal Arrangement Adaptation Era in Kupang City. This research was carried out in Elementary School in Kupang City using Mixed Methods – the combination between the quantitative and qualitatitve research with the support of survey approach. The techniques used to collect data are questionnaires, interviews, observations, and documentation studies. Data resources are: head masters, teachers, students, and the parents of the student, as well as from the whole Elementary Schools in Kupang City. The conclusions of this research are: (1) Learning management strategy applied at all Elementary School in Kupang City during the pandemic era of Covid-19 and the adaptation of new normal arrangement is online learning or both online learning and offline learning as well; (2) Education personnels in schools such as: Head masters, Teachers, Students, as well as the Students Parents of Schools responded positively and ready to apply the learning strategy, either online learning or both online and offline learning as well; (3) All schools had made their own efforts to supply the health facilities and students arrangement to facilitate and to fulfill the students need to learn and avoid the rise of new cluster of Covid-19 pandemic.